Aspergillosis in Cats: ABCD guidelines on prevention and management. Issue 7 (July 2013) - Hartmann, Katrin; Lloret, Albert; Pennisi, Maria Grazia; Ferrer, Lluis; Addie, Diane; Belák, Sándor; Boucraut-Baralon, Corine; Egberink, Herman; Frymus, Tadeusz; Gruffydd-Jones, Tim; Hosie, Margaret J; Lutz, Hans; et al.
Overview: Aspergillosis is a sporadic mycosis that occurs worldwide in mammals and birds and leads to a usually chronic, and only rarely acute, disease that mainly affects the nasal cavity and sinuses. Infection: Aspergillus species infections are commonly associated with predisposing local or systemic factors. Local disease can spread and involve the central nervous system or the lungs. Some Aspergillus species can also disseminate, causing systemic infections. In contrast to dogs, in which (nasal) aspergillosis is relatively common, aspergillosis is rare in cats, but considered an emerging infection. Clinical signs: There are two clinical forms of aspergillosis in cats, the sinonasal form (characterised by signs of chronic nasal infection) and the newly emerging, more invasive sino-orbital form (characterised by signs of orbital and surrounding tissue invasion). Sino-orbital involvement has been described now in approximately half of the reported cases. Disease management: Treatment should consist of local and systemic antifungal therapy.